2016
DOI: 10.1093/cid/ciw012
|View full text |Cite
|
Sign up to set email alerts
|

Infection Control for Drug-Resistant Tuberculosis: Early Diagnosis and Treatment Is the Key: Table 1.

Abstract: Multidrug-resistant (MDR) tuberculosis, "Ebola with wings," is a significant threat to tuberculosis control efforts. Previous prevailing views that resistance was mainly acquired through poor treatment led to decades of focus on drug-sensitive rather than drug-resistant (DR) tuberculosis, driven by the World Health Organization's directly observed therapy, short course strategy. The paradigm has shifted toward recognition that most DR tuberculosis is transmitted and that there is a need for increased efforts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 53 publications
0
53
1
3
Order By: Relevance
“…13,14 However, studies have shown that poor knowledge of TB could contribute to high burden of TB due to patients' poor health seeking behavior such as looking for inappropriate care. 15,16 Although many patients understand the need to seek care in approved health institutions, it has been shown that they do not fully assimilate the information they are receiving from the health care providers. This could be linked to lack of comprehension on TB information on the part of either the patient or nurse due to insufficient training on TB.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 However, studies have shown that poor knowledge of TB could contribute to high burden of TB due to patients' poor health seeking behavior such as looking for inappropriate care. 15,16 Although many patients understand the need to seek care in approved health institutions, it has been shown that they do not fully assimilate the information they are receiving from the health care providers. This could be linked to lack of comprehension on TB information on the part of either the patient or nurse due to insufficient training on TB.…”
Section: Discussionmentioning
confidence: 99%
“…Drug‐resistant tuberculosis has emerged as a major obstacle to gaining control over tuberculosis during recent years in China , and its comprehensive understanding is essential for formulating effective control strategies by local governments . This study shows that Hainan has a serious epidemic of drug‐resistant tuberculosis.…”
Section: Discussionmentioning
confidence: 86%
“…It is necessary to employ methods of quick diagnosis and regimens of shorter and cheaper treatment to achieve fast diagnosis and improve disease prognosis (van Cutsem et al, 2016). Such methods and regimens can be developed and/or optimized based on MDR TB animal models.…”
Section: Current Problems In Diagnosis Treatment and Prevention Of mentioning
confidence: 99%